1989
DOI: 10.1111/j.1651-2227.1989.tb17944.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Function and Morphology in Children by 99mTc‐DTPA Gamma Camera Renography

Abstract: The purpose of the present investigation was to evaluate the use of 99mTc-DTPA (diethylenetriaminepenta-acetate) gamma camera renography for the study of kidney function as well as morphology. Sixty-nine children with urinary tract infection or congenital hydronephrosis aged 6 days to 13.6 years were studied. A method for determination of the glomerular filtration rate (GFR) from the recorded curves without use of blood or urine samples was tested in 65 consecutive children. From each renogram an uptake index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…It has been well documented that the remaining renal function increases promptly after unilateral nephrec tomy [1], However, we observed that postnephrectomy compensatory renal growth varies considerably in differ ent patients [2] and might be a variable phenomenon. The aim of the study is to evaluate the age factor in compensatory renal hypertrophy after unilateral ne phrectomy with a new method, 99mTc-DTPA renogra phy, to detect the individual renal function.…”
Section: Introductionmentioning
confidence: 55%
“…It has been well documented that the remaining renal function increases promptly after unilateral nephrec tomy [1], However, we observed that postnephrectomy compensatory renal growth varies considerably in differ ent patients [2] and might be a variable phenomenon. The aim of the study is to evaluate the age factor in compensatory renal hypertrophy after unilateral ne phrectomy with a new method, 99mTc-DTPA renogra phy, to detect the individual renal function.…”
Section: Introductionmentioning
confidence: 55%
“…Seven studies evaluated 99m Tc-DMSA, 133,138,141,193,196,214,217 and one study evaluated 123 I-hippuran. 218 Half of these studies did not include an appropriate spectrum of patients.…”
Section: Static Renal Imagingmentioning
confidence: 99%
“…218 Half of these studies did not include an appropriate spectrum of patients. The quality of reporting was poor: the majority of studies (6/8) did not report patient selection criteria; 133,138,141,193,196,214 five studies provided inadequate description of the reference standard and/or the index test; 133,193,196,217,218 half of all studies did not report sufficient information to assess the avoidance of test review bias, 133,141,196,214 and four studies did not report sufficient information to assess avoidance of disease progression bias. 133,214,217,218 Disease progression bias was a problem in two studies 141,196 and partial verification bias in another study.…”
Section: Static Renal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Camera-based methods for measuring renal uptake of Tc-99m DTPA without blood or urine sampling have been widely used [6]. The method introduced by Gates [7] has been the most common routine method [8,9].…”
Section: Introductionmentioning
confidence: 99%